Musical experience and sharing musical haptices - Russ Palmer; Riitta Lahtinen; Stina Ojala (Netherlands, 2022)
In this article we introduce a systematic, holistic way of experiencing music performances through touch. This method called social-haptic communication, which consists of various touch messages called haptices is frequently used in interpreting for sensory impaired people, but can also be applied to various other disability groups, especially in connection to therapeutic approaches. Haptices are mostly used in interpreting visual events, but here we expand the scope into acoustic events, more specifically into interpretation of music. In this article we use a concert as an example of the versatility of haptices in sharing a music experience. The various techniques used in training to use haptices with music are also explained in further detail.
Procedia Social and Behavioral Sciences